Orange juice allied to a reduced-calorie diet results in weight loss and ameliorates obesity-related biomarkers: A randomized controlled trial - Ribeiro, Carolina [UNESP]; Dourado, Grace [UNESP]; Cesar, Thais [UNESP] (Elsevier, 2017)
Objective Assumptions have linked orange juice (OJ) consumption with weight gain and adverse effects on health due to its sugar content; however, epidemiologic studies have not shown increased risk for overweight or obesity with the consumption of 100% OJ. The aim of this study was to verify whether the combination of a reduced-calorie diet (RCD) and 100% OJ contribute to weight loss, promote changes in glucose and lipid metabolism, and improve diet quality in obese individuals. Methods A randomized controlled trial with 78 obese patients (age 36 ± 1 y, body mass index [BMI] 33 ± 3 kg/m2) were enrolled in two groups: Individuals in the OJ group submitted to an RCD that included OJ (500 mL/d), and individuals in the control group submitted to an RCD without OJ. Body composition, biochemical biomarkers, and dietary intake were analyzed over a 12-wk period. Results Both treatments had similar outcomes regarding body weight (−6.5 kg; P = 0.363), BMI (−2.5 kg/m2; P = 0.34), lean mass (−1 kg; P = 0.29), fat mass (−5 kg; P = 0.58), body fat (−3%; P = 0.15), and waist-to-hip ratio (−0.1; P = 0.79). Insulin levels in the OJ group decreased by 18% (P = 0.05), homeostasis model assessment–insulin resistance by 33% (P = 0.04), total cholesterol by 24% (P = 0.004), low-density lipoprotein cholesterol by 24% (P ≤ 0.001), and high-sensitivity C-reactive protein levels by 33% (P = 0.001) compared with the control group. Consumption of energy and nutrients was similar between the two groups, but vitamin C and folate increased by 62% (P ≤ 0.015) and 39% (P = 0.033), respectively, after OJ intervention. Conclusion When consumed concomitantly with an RCD, OJ does not inhibit weight loss; ameliorate the insulin sensitivity, lipid profile, or inflammatory status, or contribute nutritionally to the quality of the diet.
Keywords: Biochemical biomarkers; Body composition; Obese; Orange juice; Randomized-controlled trial; Reduced-calorie diet